Perbedaan Sikap Keberagamaan Antara Masyarakat Islam dan Kristiani di Sumatera Utara dan Frankfurt Am Main Jerman - Irwansyah Irwansyah (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2014)
This article seeks to reveal differences of religious attitudes between Muslim and Christian communities in North Sumatera and Frankfurt Am Main Germany. This article shows that the relation between Muslims and Christians can be understood to have taken place in two categories, positive and negative. Positive relation can be attested through integrating factors between the two religious communities, while negative relation can be attested through separating factors. In North Sumatera there exist local wisdoms which serve as adhesive factors of Muslim-Christian relation, such as the concept of ?marga? among Batakese society. Meanwhile, pig either as food or as pet is regarded as a dividing factor together with fanaticism and exclusivism. In Germany, as majority group the Christians are tolerant towards Muslims due to the rule of law in the country. This tolerance becomes an adhesive factor, while mutual suspicion among both Muslims and Christians is raeagrded as dividing factor.